Earth jurisprudence : private property and the environment - Burdon, Peter (Milton Park, Abingdon, Oxon : Routledge, 2015)
'Earth Jurisprudence: Private Property and the Environment argues that the institution of private property is anthropocentric and needs to be reconceived. The dominant rights-based interpretation of private property entrenches the idea of human dominion over nature. Accordingly, nature is not attributed any inherent value and becomes merely the matter of a human property relationship. This book considers how an alternative conception of property might be grounded in the eco-centric concept of an Earth community. Recognising that human beings are deeply interconnected with and dependent on nature, this concept is proposed as a standard and measure for human law. Using the theory of Earth Jurisprudence as a guide, this book then outlines an alternative eco-centric description of private property, as a relationship between and among members of the Earth community. Drawing on international case law, indigenous views of property and the land use practices of agrarian communities, this concept is then employed to consider how private property can be reformulated in a way that fosters duties towards nature.'--
'The dominant rights-based interpretation of private property entrenches the idea of human dominion over nature. Accordingly, nature is not attributed any inherent value and becomes merely the matter of a human property relationship. Earth Jurisprudence: Private Property and the Environment explores how an alternative conception of property might be instead grounded in the eco-centric concept of an Earth community. Recognising that human beings are deeply interconnected with and dependent on nature, this concept is proposed as a standard and measure for human law. Using the theory of Earth Jurisprudence as a guide, this book outlines an alternative eco-centric description of private property, as a relationship between and among members of the Earth community'--
'A GlassHouse book'
Includes bibliographical references (pages 137-163) and index.
Keywords: Right of property; Environmental law -- Philosophy; Property; Conservation of natural resources -- Law and legislation; Law -- Philosophy